Synthesis and Characterization of 2,3-Diaminomaleonitrile Derivatives by One-Pot Schiff Base Reaction and Their Application in Dye Synthesized Solar Cells - Saifaldeen Muwafag Abdalhadi; Asmaa Yahya Al-Baitai; Hazim Abdulrazzaq Al-Zubaidi (Universitas Gadjah Mada, 2021)
In a one-pot reaction, three new 2,3-diaminomaleonitrile (DAMN) derivative dyes were prepared by simple Schiff base reaction. The compounds were designed as a sensitizer in dye synthesizes solar cells (DSSCs). Many conditions have been used to provide the methodology to get the best yield. The prepared dyes were characterized by melting point, elemental microanalysis, mass spectroscopy, FT-IR, 1H-NMR, and UV-Vis spectroscopy. A computational study was carried out to support our results. The DSSC data was shown the best performance for SA3 dye with 0.38% efficiency at AM 1.5 then SA2 with 0.22% and the last dye is SA1 with 0.09%, compared to control cell (N719) 5.4%.